Limited Search and the Technology Choices of Multinational Firms in Brazil* - Morley, Samuel A.; Smith, Gordon W. (Quarterly Journal of Economics, 1977)
I. Introduction 263.—II. Limited search and technology transfer, 265.—III. Empirical results, 271.—IV. Policy implications, 286.